Literatur Review, Faktor Keberhasilan Dan Kegagalan Implementasi Six Sigma Di Beberapa Negara - Sugeng Budi Raharjo; Ismasari Nawangsih; Adi Rusdi Widya (DPPM Universitas Pelita Bangsa, 2022)
The Six sigma method is a method for improving the achievement of quality by means of a breakthrough, where the old model by means of Continuous Improvement cannot achieve a very critical target, namely 6 sigma, or 3.4 million defects from 1 million production or operations. Six sigma techniques have been implemented in many countries, first developed in 1986 by Bill Smith, Engineer at Motorola. Since then, it has been applied in many countries, because of its very effective use, especially such as the Aircraft Industry, Health Industry, and others that require reliability of up to 99, 999%. How about in Indonesia? Several companies have implemented this system, especially foreign companies, which are affiliated with Indonesian companies, as well as companies that have ventured overseas. This study uses quantitative research, by analyzing the Literature Review of the success of the Six Sigma program in the company based on the Leader's Vision and Mission, Organizational Culture, Discipline in running the program and the success of program implementation. Sampling of research was 60 international journals, and after in-depth research on 15 journals the following findings were found: There are four factors that have the greatest impact, namely (1) the need for top management commitment to the running of the Six Sigma program (2) training needs for the green belt team in the success of Six Sigma (3) Infrastructure needs to support the running of the Six Sigma program (4) The need for other supports such as: Business Strategy Linkages, Relationships with Customers, Changes in Organizational Culture and the need for Six Sigma Team Competencies Keywords: Six Sigma, Industrial Sector, Organizational Culture, Effectiveness of Program Implementation